علاقة الثقافة التنظيمية بالالتزام التنظيمي - ضو, أم الخير; خالدي, فتيحة (University of Eloued جامعة الوادي, 2023)
الملخص تهدف الدراسة الى التعرف على علاقة الثقافة التنظيمي بالالتزام التنظيمي بمؤسسة بريد الجزائر بالوادي، ولبلوغ الهدف، فقد تناولنا في الفصل الأول اهم المفاهيم المرتبطة بموضوع الدراسة من الثقافة التنظيمية والالتزام التنظيمي، في حين تضمن الفصل الثاني الدارسة الميدانية، وقد تم الاعتماد على المنهج الوصفي التحليلي، وعلى الاستبيان كأداة أساسية للحصول على المعلومات والاستعانة بالعديد من الأساليب الإحصائية لتحديد طبيعة البيانات واختبار البيانات. وقد توصلت الدراسة الى وجود علاقة بين الثقافة التنظيمية والالتزام التنظيمي، ووجود علاقة بين ابعاد الثقافة التنظيمية (القيم التنظيمية، الأعراف التنظيمية، المعتقدات التنظيمية) والالتزام التنظيمي. الكلمات المفتاحية: الثقافة التنظيمية، الالتزام التنظيمي. Abstract The study aims to identify the relationship of organizational culture with organizational commitment at the Algeria Post Corporation in El-Oued, and to achieve the goal, we have dealt in the first chapter with the most important concepts related to the subject of the study of organizational culture and organizational commitment, while the second chapter included the field study, and the descriptive analytical approach has been relied upon. And the questionnaire as a basic tool for obtaining information and the use of many statistical methods to determine the nature of the data and test the data. The study concluded that there is a relationship between organizational culture and organizational commitment, and there is a relationship between the dimensions of organizational culture (organizational values, organizational norms, organizational beliefs) and organizational commitment. Keywords: organizational culture, organizational commitment.
دراسة ميدانية بمؤسسة بريد الجزائر بالوادي - البريد المركزي -
مذكرة ماستر في علم الاجتماع تخصص تنظيم وعمل
Keywords: الثقافة التنظيمية، culture organisationnelle, organizational culture; الالتزام التنظيمي، l'engagement organisationnel, organizational commitment